'In case of emergency press here': framing geoengineering as a response to dangerous climate change. (2nd December 2013) - Markusson, Nils; Ginn, Franklin; Singh Ghaleigh, Navraj; Scott, Vivian
Abstract : Geoengineering, especially its potentially fast and high‐leverage versions, is often justified as a necessary response to possible future climate emergencies. In this article, we take the notion of 'necessity' in international law as a starting point in assessing how rapid, high‐leverage geoengineering might be justified legally. The need to specify reliably 'grave and imminent peril' makes such a justification difficult because our scientific ability to predict abrupt climate change, for example, as tipping elements, is limited. The time it takes to establish scientific consensus as well as policy acceptance restricts the scope for effective forewarning and so pre‐emptive justifications for geoengineering become more tempting. While recognizing that dangerous, large‐scale impacts of climate change is becoming increasingly difficult to avoid, the pre‐emptive, emergency frame is problematic. We suggest that arguments from emergency operate on a high level of uncertainty and tend toward hubristic attempts to shape the future, as well as tending to close down rather than open up space for deliberation. We conclude that the emergency frame is not likely to go away, that ignoring or repressing it is a dangerous response, and that more effort is required to defuse and disarm emergency rhetoric. WIREs Clim Change 2014, 5:281–290. doi: 10.1002/wcc.263 This article is categorized under: Policy and Governance > Multilevel and Transnational Climate Change Governance Social Status of Climate Change Knowledge > Climate Science and Decision Making